Estimativas de consumo de bovinos a pasto utilizando o caulim como indicador fecal - Luana Silva Caramalac (2021)
Many markers have limitations, kaolin is a possible intake marker with applicability, because it has acceptable physical and chemical characteristics. The quantification is performed indirectly by aluminum present in the substance, and determined by colorimetric method with aluminon. Currently, research in animal nutrition has presented interesting information, however, flaws in the analytical methodology of kaolin have shown unsatisfactory results. An effective alternative is nitroperchloric acid digestion associated with hydrofluoric acid. So, research for new practical and low-cost methodologies that present accurate and robust results is still necessary. Manuscript 2: We tested a new Al extraction analytical procedure in kaolin samples and compared the results with samples analyzed by the aluminon colorimetric method and reading by optical emission spectroscopy with inductively coupled plasma. The samples were digested in a nitroperchloric acid mixture associated with hydrofluoric acid, and quantified by atomic absorption spectrophotometry. Therefore, the analytical procedure proposed by the study was accurate and robust regarding Al extraction from samples of cattle feces with kaolin. Manuscript 3: Exp. 1 The objective was to replaced titanium dioxide with kaolin, supplied orally, as fecal markers, while chromic oxide was used as a marker of supplement intake. Three sequential trials were conducted, and in each trial used four Nelore steers, which received individually and simultaneously 20 g TiO2 and 80 g kaolin/animal orally and 2.0 kg of supplement containing 1% chromic oxide. To evaluate the difference between different times of collection of feces were collected feces at two times (08:00 am and 16:00 pm), after performing a composite sample of these. There were no significant differences (P=0.7976) in the determination of fecal excretion when determined by the external markers titanium dioxide and kaolin. When the final results were compared by collecting feces at different times, there was no significant effect between the estimated values. It was concluded that kaolin was able to estimate the fecal excretion of beef cattle on pasture, and the management of collecting feces once a day is sufficient to estimate the nutritional evaluations of them. In Exp. 2, we evaluated the possibility of replacing titanium dioxide with kaolin, supplied via supplement, as markers of fecal excretion in beef cattle grazing (4 steers/study; 360 days of age). It was observed that kaolin showed superior results (P ≤ 0.0002) to that estimated by TiO2 (2.70 and 5.25 kg/d, respectively). Concluded that the supply via supplement of the external marker kaolin, did not allow the estimation of fecal excretion of calves. Manuscript 4. Two simultaneous experiments were performed to evaluate the substitution of LIPE® as an estimator of fecal excretion, and of chromic oxide as an estimator of supplement intake by kaolin (Exp. 1) and titanium dioxide (Exp. 2). Twelve Nelore steers were used (4 steers/treatment; 233 ± 6.2 kg of BW). Thus, the external markers kaolin and TiO2, were able to estimate the fecal excretion and dry matter consumption of beef cattle to pasture.